Effects of Spinal Cord Stimulation on Heart Rate Variability in Patients With Failed Back Surgery Syndrome: Comparison Between a 2‐lead ECG and a Wearable Device. Issue 3 (25th December 2019) - Goudman, Lisa; Brouns, Raf; Linderoth, Bengt; Moens, Maarten
Abstract : Objectives: Heart rate variability recordings have the potential to examine the role of the autonomic nervous system. Several wearable devices are nowadays readily available. Up until now, no studies explored whether a wearable device is able to reliably measure a treatment response in chronic pain patients. Therefore, the aim of this study is to evaluate the reliability of a Polar V800 (Polar Electro Oy, Finland) wearable device to accurately measure RR intervals in patients with failed back surgery syndrome (FBSS) during spinal cord stimulation (SCS), as compared with an eMotion 2‐lead ECG recording. Materials and Methods: Twenty‐two patients diagnosed with FBSS and treated with SCS participated in this study. HRV was measured with a 2‐lead ECG registration tool and a Polar V800 during on and off state of SCS. Intraclass correlation coefficients, correlations, limits of agreement, Cronbach's α, and effect sizes were calculated. Results: Analysis based on the recordings from the ECG and wearable device revealed the same HRV parameters (except for the time‐frequency domain) to capture the treatment response of SCS. Parameters that are relevant for measuring the SCS treatment response have strong correlations ( r  ≥ .82), good ICC values (ICC ≥0.82), acceptable consistency ( α  ≥ .9), and limited bias. Conclusions: Similar pre‐ to posttreatment changes were revealed between a wearable device and 2‐lead ECG with reliable HRV estimates for parameters that are able to capture the treatment changes. This suggests that a wearable heart rate monitor might be a reliable wearable tool for the detection of pre‐ to post treatment changes of SCS, in patients with FBSS.